Involvement of nitrate reductase (NR) in osmotic stress-induced NO generation of Arabidopsis thaliana L. roots - Kolbert, Zsuzsanna; Ortega, Leandro Ismael; Erdei, László (Elsevier, 2020)
Nitric oxide (NO) is undoubtedly a potential signal molecule in diverse developmental processes and stress responses. Despite our extensive knowledge about the role of NO in physiological and stress responses, the source of this gaseous molecule is still unresolved. The aim of this study was to investigate the potential role of nitrate reductase (NR) as the source of NO accumulation in the root system of wild-type and NR-deficient nia1, nia2 mutant Arabidopsis plants under osmotic stress conditions induced by a polyethylene glycol (PEG 6000) treatment. Reduction of primary root (PR) length was detected as the effect of osmotic stress in wild-type and NR-deficient plants. We found that osmotic stress-induced lateral root (LR) initiation in wild-type, but not in NR-mutant plants. High levels of NO formation occurred in roots of Col-1 plants as the effect of PEG treatment. The mammalian nitric oxide synthase (NOS) inhibitor NG-monomethyl-l-arginine (l-NMMA) had no effect on LR initiation or NO generation, while tungstate, an NR inhibitor, inhibited the later phase of osmotic stress-induced NO accumulation and slightly decreased the LR development. In nia1, nia2 roots, the PEG treatment induced the first phase of NO production, but later NO production was inhibited. We conclude that the first phase of PEG-induced NO generation is not dependent on NOS-like or NR activity. It is also suggested that the activity of NR in roots is required for the later phase of osmotic stress-induced NO formation.